Murine interferon-beta receptor-mediated endocytosis and nuclear membrane binding. - Kushnaryov, V M (1985)
Radioiodinated mouse interferon-beta (125I-MuIFN-beta) bound with high affinity (Kd = 9.8 X 10(-10) M) to plasma membrane of L929 murine fibroblasts (4-6 X 10(3) receptor sites per cell). The binding was saturable and inhibited by a 100-fold excess of unlabeled MuIFN-beta but not by excess mouse IFN-gamma (MuIFN-gamma). MuIFN-beta bound at 4 degrees C was very rapidly internalized upon warming of the cells to 37 degrees C (t 1/2 = 1.5 min). Indirect immunoferritin labeling indicated that MuIFN-beta was initially located in coated pits and subsequently internalized by receptor-mediated endocytosis. Isolated L929 cell nuclei bound 125I-MuIFN-beta with a 7-fold higher affinity (Kd = 1.4 X 10(-10) M) and higher receptor density (about 10(4) per nucleus) than that for the plasma membrane. Binding to the nuclear membrane was inhibited by a 100-fold excess of unlabeled MuIFN-beta but not by excess MuIFN-gamma. Trypsin treatment of nuclei decreased IFN binding by 80%, suggesting that the putative nuclear receptors are protein. Specific binding of MuIFN-beta to nuclei was also shown by fluorescence and electron microscopy. We propose that the very rapid internalization of MuIFN-beta by receptor-mediated endocytosis is important in the cellular processing of IFN and that its high-affinity binding to the nuclear membrane suggests the nucleus as an intracellular site of IFN action.